Peningkatan Keterampilan Membaca Pemahaman Siswa Sekolah Dasar Melalui Implementasi Model CIRC Berbantuan Media Cetak - Vina Anggia Nastitie Ariawan; Niken Tri Utami; Rahman Rahman (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2018)
One of effort to solve the low reading skill of students is through the implementation of innovative learning models. This research aims to enhance primary students’ reading comprehenssion by implementing CIRC model within printed media. This research used collaborative action research of Kemis & Mc Taggart model. Participants of this research were 20 students at one of primary school in Karangpucung Sub-district. Researcher employed teacher as opponent participant to implementing action research and obtain supplementary dataTechnique of collecting data used observation, interview, test, and observation and interview is used to obtain data about the implementation of research. Meanwhile, test is used to measure students’ reading comprehenssion skill. Researcher analyzed data with three steps namely data reduction, displaying data, and drawing conclusion. In addition, triangulation technique is used to validating data. The research outcome showed the enhance of reading comprehenssion skill in each cycle. Based on the research outcome, researcher concludes that the implementation of CIRC model within printed media can enhance reading comprehenssion skill of primary students.